Granulomatosis with polyangiitis involving the epiglottis. Issue 3 (1st March 2017) - Aono, Yuya; Imokawa, Shiro; Uto, Tomohiro; Sato, Jun; Tanioka, Fumihiko; Suda, Takafumi
Abstract : Granulomatosis with polyangiitis (GPA) frequently involves the upper respiratory tracts, but involvement of the epiglottis is extremely rare. This report describes a patient initially presenting with dysphagia and increasing stridor due to epiglottitis. Bronchoscopy showed swelling of the epiglottis with partly whitish nodular lesions, with biopsy specimens showing neutrophil infiltration and necrosis. Chest computed tomography showed multiple nodular consolidations in the bilateral lung parenchyma, and histological findings were consistent with vasculitis. The patient was diagnosed with GPA and responded well to treatment with prednisolone and cyclophosphamide. Although an uncommon manifestation, GPA should be included in the differential diagnosis of epiglottitis, especially in patients with lung parenchymal lesions suggestive of GPA. Abstract : Granulomatosis with polyangiitis (GPA) frequently involves the upper respiratory tracts, but involvement of the epiglottis is extremely rare. This report describes a patient initially presenting with dysphagia and increasing stridor due to epiglottitis associated with GPA.